An organelle-directed chemical ligation approach enables dual-color detection of mitophagy. Issue 11 (2nd November 2021) - Shi, Yilong; Zou, Xiaoxue; Wen, Shixiong; Gao, Lei; Li, Jian; Han, Jiahuai; Han, Shoufa
ABSTRACT: Dysfunctional organelles and defective turnover of organelles are engaged in multiple human diseases, but are elusive to image with conventional organelle probes. To overcome this, we developed intra-mitochondrial CLICK to assess mitophagy (IMCLAM), using a pair of conventional ΔΨm probes, where each probe alone fails to track dysfunctional mitochondria. The in situ formed optical triad is stably trapped in mitochondria without resorting to ΔΨm. Utilizing an acidity-responsive ΔΨm probe, IMCLAM enabled fluorescence-on detection of mitophagy by sensing pH acidification upon delivery of mitochondria into lysosomes. Moreover, we applied IMCLAM to assay mitophagy induced by pharmacological compounds in living cells and wild-type zebrafish embryos. Thus, IMCLAM offers a simplified tool to study mitochondria and mitophagy and provide a basis for screening mitophagy-inducing compounds. Abbreviations: CCCP, carbonyl cyanide m-chlorophenylhydrazone; IMCLAM, intra-mitochondrial CLICK to assess mitophagy; ROX, X-rhodamine; SPAAC, stain-promoted azide-alkyne Click Chemistry; TPP, triphenylphosphonium. Graph abstract: uf0001